Assessing recent reforms and policy directions in France. Implementing the OECD Jobs Strategy - Carcillo, Stéphane; Goujard, Antoine; Hijzen, Alexander; Thewissen, Stefan (Paris, 2019)
"The OECD actively supports countries with the implementation of the OECD Jobs Strategy through the preparation of labour market chapters in the OECD Economic Surveys. This paper provides an overview of the analytical work carried out in the context of the 2019 Economic Survey for France. The paper consists of a preliminary assessment of the French labour market reforms since 2017 related to the tax and benefit system, employment protection, and collective bargaining. These reforms are broadly in line with the recommendations of the OECD Jobs Strategy. They are likely to contribute to enhanced employment and living standards of low-skilled workers and reduce labour market duality. However, a close monitoring will be necessary to assess whether their implementation has the desired effects and additional measures are needed."